Effectiveness of first‐line cetuximab in wild‐type RAS metastatic colorectal cancer according to tumour BRAF mutation status from the EREBUS cohort. Issue 3 (15th September 2020) - Rouyer, Magali; François, Eric; Sa Cunha, Antonio; Monnereau, Alain; Bignon, Emmanuelle; Jové, Jérémy; Lassalle, Régis; Droz‐Perroteau, Cécile; Moore, Nicholas; Noize, Pernelle; Fourrier‐Réglat, Annie; Smith, Denis
Abstract : Aims: Poor efficacy has been reported for patients with BRAF mutations for metastatic colorectal cancer (mCRC). Methods: EREBUS is a French cohort study of wild‐type (wt) KRAS unresectable mCRC patients initiating a first‐line treatment with cetuximab from 2009 to 2010, followed for two years (five years for vital status). Molecular genetics platforms have provided additional RAS and BRAF mutation testing results. Progression‐free survival (PFS) and overall survival (OS) were assessed according to tumour mutation (mt) status: RAS mt/ BRAF any, RAS wt/ BRAF mt and RAS wt/ BRAF wt. Multivariate Cox analyses were used to evaluate association between mutation status and death or progression. Results: A total of 389 patients were included in 65 centres and with a known tumour mutation status: 64 RAS mt/ BRAF any (21%), 33 RAS wt/ BRAF mt (13%) and 213 RAS wt/ BRAF wt (87%). Respective baseline characteristics were: median age 65, 64 and 63 years, male gender 63%, 64% and 69%, Eastern Cooperative Oncology Group performance status ≤ 1 75%, 76% and 79%, and liver‐only metastases 39%, 33% and 40%. Median progression‐free survival was 8.0 months [5.9–9.3] for patients with RAS mt/ BRAF any, 6.0 months [2.3–7.2] for patients with RAS wt/ BRAF mt, and 10.4 months [9.5–11.0] for patients with RAS wt/ BRAF wt. Respectively, median overall survival was 18.4 months [10.9–23.3], 9.7 months [6.9–16.6] and 29.3 months [26.3–36.1]. In multivariate analyses, progression (HR = 2.71 [1.79–4.10]) and death (HR = 2.79 [1.81–4.30]) were more likely for RAS wt/ BRAF mt vs RAS wt/ BRAF wt patients. Conclusions: BRAF mutations were associated with markedly poorer outcomes in initially unresectable RAS wt mCRC patients treated by cetuximab in first‐line treatment.